High resuscitative endovascular balloon occlusion of the aorta procedural volume is associated with improved outcomes: An analysis of the AORTA registry. Issue 5 (November 2021) - Gorman, Elizabeth; Nowak, Brittany; Klein, Michael; Inaba, Kenji; Morrison, Jonathan; Scalea, Thomas; Seamon, Mark; Fox, Charles; Moore, Laura; Kauvar, David; Spalding, Marshall; Dubose, Joseph; et al.
Abstract : BACKGROUND: The use of resuscitative endovascular balloon occlusion of the aorta (REBOA) is controversial. We hypothesize that REBOA outcomes are improved in centers with high REBOA utilization. METHODS: We examined the Aortic Occlusion in Resuscitation for Trauma and Acute Care Surgery registry over a 5-year period (2014–2018). Resuscitative endovascular balloon occlusion of the aorta outcomes were analyzed by stratifying institutions into low-volume (<10), average-volume (11–30), and high-volume (>30) deployment centers. A multivariable model adjusting for volume group, mechanism of injury, signs of life, systolic blood pressure at initiation, operator level, device type, zone of placement, and hemodynamic response to aortic occlusion was created to analyze REBOA mortality and REBOA-related complications. RESULTS: Four hundred ninety-five REBOA placements were included. High-volume centers accounted for 63%, while low accounted for 13%. High-volume institutions were more likely to place a REBOA in the emergency department (81% vs. 63% low volume, p = 0.003), had a lower mean systolic blood pressure at insertion (53 ± 38 vs. 64 ± 40, p = 0.001), and more Zone I deployments (64% vs. 55%, p = 0.002). Median time from admission to REBOA placement was significantly less in patients treated at high-volume centers (15 [7–30] minutes vs. 35 [20–65] minutes, p = 0.001). Resuscitative endovascular balloon occlusion of the aorta mortality was significantly higher at low-volume centers (67% vs. 57%; adjusted odds ratio, 1.29; adj p = 0.040), while average- and high-volume centers were similar. Resuscitative endovascular balloon occlusion of the aorta complications were less frequent at high-/average-volume centers, but did not reach statistical significance (adj p = 0.784). CONCLUSION: Resuscitative endovascular balloon occlusion of the aorta survival is increased at high versus low utilization centers. Increased experience with REBOA may be associated with earlier deployment and subsequently improved patient outcomes. LEVEL OF EVIDENCE: Therapeutic/Care Management, level IV. Abstract : Supplemental digital content is available in the text.